Analysis of The Selection of Vaginal Birth After Cesarean (VBAC) Delivery Methods in the Cengkareng Area of West Jakarta - Siti Musdalifah; Rukmaini; Shinta Novelia (KHD Production, 2024)
The increase in the number of deliveries by CS causes an increase in the number of women with a history of CS for a second pregnancy and becomes a problem for subsequent types of birth. An effort to reduce the incidence of CS delivery is with Vaginal Birth After Caesarean (VBAC). Vaginal birth After Caesarean (VBAC) is a vaginal birth after a cesarean section (Cunningham, 2013). Mothers who are afraid of undergoing a normal birth process are caused by many factors, one of which is the problem of lack of information provided and support from both health workers and family regarding the choice of VBAC method. This study aimed to determine the relationship between maternal knowledge, family support, and health worker support on the choice of VBAC method at TPMB West Jakarta City in 2024. The method used in this research is observational analytics with a Cross-Sectional Study design. The sample in this study was pregnant women in the second and third trimesters with a history of 1 time non-absolutely indicated CS (such as CPD, uterine rupture). In this research, the instrument used was a questionnaire sheet. The analysis used Chi Square. There is a relationship between knowledge and the choice of delivery method, Vaginal Birth After Caesar (VBAC), the value is (p=0.000), there is a significant relationship between family support and the choice of delivery method, Vaginal Birth After Caesar (VBAC), the value is (p=0.000) and there was a significant relationship between support from health workers and the choice of delivery method. Vaginal Birth After Caesar (VBAC) was obtained (p=0.000).